A review of paediatric vision screening protocols and guidelines - Atowa, Uchenna C. (Int J Ophthalmol, 2019)
Vision screening plays an important role in the early detection of children who have or probably are predisposed to have specific visual problems. The validity and reliability of the screening batteries in relation to the age group to be screened, and the person administering the test as well as the referral and follow-up criteria contribute to the overall outcome of the vision screening. Despite the long history of vision screening and significant improvement in the development of screening protocols, no agreement exists concerning the age at which children should be screened, the exact test batteries that should be included and who should conduct the screening. This review highlights some important aspects of the history of paediatric vision screening and available evidence in support of their use to detect visual conditions in children. It also examines some of the barriers against the development of paediatric vision screening models especially in low and medium income countries.